Competition trick analysis in snowboard slopestyle and big air - Tsai, M.-C.; Chua, J.; Sheppard, J. (Journal of Human Sport & Exercise, 2023)
Snowboarding tricks are judged by execution, difficulty, amplitude, variety and progression in freestyle disciplines. In Slopestyle, an additional judging criterion termed Overall Impression (40% of final score) quantifies the flow of the run. To maximise final score, we aim to investigate the relationship between jump rotation and judging score by gender and take-off side in Slopestyle and Big Air events and the effect of individual Slopestyle features on overall impression score. Only jump features (n = 675) from 9 competitions were analysed (249 female, 426 male). Multiple linear regression was used to determine the relationship between score and trick rotations by sex and take-off side, and to determine the presence of individual feature effect on overall impression score. There was a strong linear relationship between jump rotation and score (p < .001), though at different rates of increase based on gender and take-off side. Switch frontside take-off is rewarded with the highest scores at high levels of rotation in both genders. In Slopestyle features, the last jump was found to have the highest relative importance on overall impression score (92.02%). These findings allow athletes and coaches to better design training interventions and competition strategy, while providing judges with useful information about judging patterns.